Efektivitas Kombinasi Tanaman Refugia dan Pestisida Nabati dalam Menekan Populasi Hama Thrips (Thrips Sp.) pada Tanaman Cabai Merah (Capsicum Annum L.) - Sallindri Apalle; Nanang Tri Haryadi (Jember University Press, 2023)
The purpose of this study was to determine the effect of a combination of refugia plants and botanical pesticides in suppressing the number of thrips on red chili plants. This research was conducted in October 2022-March 2023 in paddy fields, Sukorejo Village, Bangsalsari District, Jember Regency. The experimental design used was a randomized block design (RBD) with 4 treatments and 4 repetitions. The variables observed in this study were thrips pest population, pest attack intensity and chili production. The data obtained from the observed variables was then analyzed by ANOVA (Analysis of Variance) and to determine the effect between treatments, the Duncan Multiple Range Test (DMRT) was carried out at 5% level. Based on the results of the research, it was shown that the use of a combination of refugia plants and vegetable pesticides had a very significant effect on the observed variable of red chili fruit production and had a significant effect on the intensity of pest attacks, but showed no significant effect on thrips pest populations. Red chili plants with P3 treatment (marigold and tobacco leaf pesticides) had a significant effect in reducing the intensity of pest attacks and increased red chili fruit production, while chili plants treated with P2 (kenikir and tobacco leaf pesticides) had a significant effect in reducing thrips pest populations.